HUBUNGAN SOSIAL EKONOMI AKSEPTOR KB DAN ADA TIDAKNYA TOKOH PANUTAN DENGAN PENGGUNAAN IUD - Isnaini Avia Nita; Dharminto Dharminto; Farid Agusyahbana; Yudhy Dharmawan (Jurnal Kesehatan Masyarakat (Undip), 2018)
Intra Uterine Device (IUD) is a contraceptive device installed in the uterus that is relatively more effective when compared with pill, injection and condom methods. Socioeconomic factor is  one of the factors that determine a person in choosing and using contraception. The high cost of living, the limited opportunities and employment and education for women have changed the perceptions and decisions to use IUD contraception. The pattern of dependence on the group is still strong enough in this village so that if one is using MKJP and succeed then it can attract other acceptors to move.The purpose  of this study was to analyze the socioeconomic relationship of family planning acceptors and the presence of role models with the use of IUDs on  family planning  Active. The research method used in this study was explanatory research using cross sectional study approach. Population in this study were 715 people with88  sample, who where chosen by  simple random sampling technique.There were three analyses used in this study; univariate analysis, using cross tabulation and chi square test. The result of univariate analysis showed that 51.1% respondents had moderate socioeconomic status, who had a role model (65.9%) and 75% of respondents included in Non IUD and 25% of respondents using IUD. The result of bivariate analysis revealed that there was a significant relationship among socio-economic with the use of IUD (p value = 0.001), and there was  not significant relationship among there were no role models with IUD use (p value = 0.299). This study encourages other researchers to have more research on it. This study also suggests to increase the coverage of IUD users on acceptors pay more attention to their social economy in order for continuing the program..